DEVELOPMENT AND IN-VITRO EVALUATION OF NICOTINE TROCHES FOR SMOKING CESSATION - pothu, Renuka; Rao Yamsani, Madhusudan (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Nicotine replacement therapy is a way of getting nicotine into bloodstream without smoking. The present investigation aims to design, prepare and evaluate compressed tablet lozenges or troches of nicotine 2mg for low dependent smokers and, 4mg for high dependent smokers, sugar free troches. The benefits of these prepared lozenges are increased bioavailability, reduction in gastric irritation by reducing first pass metabolism. Method: The lozenges were prepared by wet granulation method. Results and discussion: All the formulations prepared were subjected to various physico-chemical parameters like hardness, content uniformity, friability, weight variation etc. The prepared formulations have a hardness of 9-12 Kg. /cm². Sugar free troches with kyron T 114 (1:4 molar ratio) for 2mg and (1:6 molar ratio) for 4mg showed decreased burning after taste and pungent odor and provided good taste. Stability study of selected formulations was also carried out at 37ºC for a period of six months. Selected formulations were tested for drug excipient interactions subjecting to FTIR Spectral analysis. In-vitro drug dissolution studies showed 100% for optimized formulations. Conclusions: Sugar free troches are useful for diabetic smokers. Troches can provide an attractive alternative formulation in the Nicotine replacement therapy. Key words: Nicotine; Troches; Lozenges; Hydroxyl Propyl Methyl Cellulose